2019
DOI: 10.3892/ol.2019.10190
|View full text |Cite
|
Sign up to set email alerts
|

Study on value of ultrasonic elastography in diagnosis of clinical staging of cervical cancer and efficacy evaluation of radiotherapy

Abstract: The aim of this study was to investigate the application of ultrasonic elastography in the diagnosis of the clinical staging of cervical cancer (CC) and its evaluation value of the treatment effect of CC. A total of 160 suspected CC patients treated in our hospital from September 2016 to March 2018 were collected. Transvaginal conventional ultrasound and ultrasonic elastography were performed on patients to compare the results of the two in the diagnosis of the pathology and clinical staging of CC. Radiotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In this kind of population, most cervical lesions will subside naturally with the clearance of infection. The body's immunosuppression can increase the risk of HPV infection, such as immune system defect AIDS [ 5 , 6 ]. There is a close relationship between HPV and cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In this kind of population, most cervical lesions will subside naturally with the clearance of infection. The body's immunosuppression can increase the risk of HPV infection, such as immune system defect AIDS [ 5 , 6 ]. There is a close relationship between HPV and cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The Cs means were 2.05 ± 0.77 m/s (endometrium) while 2.82 ± 0.77 m/s(myometrium) Lesions of the uterus 2022 Pongpunprut et al [ 33 ] NM = 25, UF = 25, AM = 25 SWE Prospective cross-Sectional Study Cs mean The Cs differed between NM and AM ( p = 0.019) with the cut-off point at 3.465 m/s and 80% sensitivity, 80% specificity, and AUC of 0.80 (95% CI 0.68–0.93) ( p < 0.001). SWE could not differentiate AM from UF or UF from NM 2021 Görgülü et al [ 34 ] UF = 98, AM = 37 NM = 40 SWE, SE and MRI ADC Retrospectively case–control study SR mean, SR max, ADC values, Cs mean, and Cs max SE, SWE, and MRI ADC could be useful in differentiating UF and AM ( p < 0.001 for all three), and none of these methods were statistically superior to each other in differentiating the UF from the AM ( p < 0.001) 2019 Zhang et al [ 49 ] NM = 16, UF = 12, AM = 6 SWE Prospective case–control study Cs mean Cs mean in NM was 4.861.9 m/s, compared with 4.962.5 m/s in AM and 5.662.5 m/s in UF ( p = 0.34). SWV for AM and UF did not differ significantly ( p = 0.40) 2018 Bildaci et al [ 29 ] AM = 28, NM = 62 vitro ARFI Prospective case–control study Cs mean The Cs mean of AM (4.22 ± 1.62 m/s) showed a significant difference compared to that of NM (3.22 ± 0.90 m/s) ( p < 0.01) 2018 Stoelinga et al [ 30 ] NM = 10, UF = 10, AM = 10 SE Prospective diagnostic study Uterine volume for AM and fibroid volume for AF The sensitivity of SE in the diagnosis of UF and AM was 82% and 91%, and the specificity was 95% and 97% with high inter-observer and inter-method agreement 2018 <...…”
Section: Normal Myometrium Uterine Fibroids and Adenomyosismentioning
confidence: 99%
“…Radiotherapy was used for patients confirmed as CC75 in 160 suspected CC patients. The results demonstrated that SE has a certain clinical value in the diagnosis and efficacy evaluation of CC, and its sensitivity (94.67%), specificity (92.94%), and diagnostic accordance rate (93.75%) [ 49 ]. In 2021, Shao et al conducted a systematic review of the UE application in CC and concluded that both SE and SWE might have important roles in the differential diagnosis of CC, assessment of the degree of invasion, clinical staging, and early evaluation of treatment effects [ 50 ].…”
Section: Cervical Tumorsmentioning
confidence: 99%
“…Cervical cancer is the fifth most common malignant tumor in women, and it is also one of the most common causes of cancer deaths in women, especially in underdeveloped countries [1][2][3]. e treatment of cervical cancer and after surgery mainly depends on the tumor stage [4,5].…”
Section: Introductionmentioning
confidence: 99%